CADD-48. microRNA-34a PACKAGED IN BACTERIAL NANOCELLS OVERCOMES THERAPEUTIC RESISTANCE IN GLIOBLASTOMA. (5th November 2018) - Babar Khan, Muhammad; Ruggieri, Rosamaria; Tran, Nhan; Sarkaria, Jann; MacDiarmid, Jennifer; Brahmbhatt, Himanshu; Boockvar, John; Symons, Marc
Abstract: microRNA-34a could serve as a novel therapeutic agent since it is under-expressed in Glioblastoma and modulates the expression of multiple genes in the deregulated p53, Rb and receptor tyrosine kinase networks which confer selective growth advantage and represent significant intra-tumoral heterogeneity, a major cause of therapeutic resistance. We studied the effects of microRNA-34a transfection in three primary patient-derived lines (GBM 6, GBM118 and GBM 126, respectively belonging to classical, mesenchymal and proneural subtypes), four established cell lines (T98G, U251, A172, LN229; where T98G and U251 show primary resistance to treatment while A172 and LN229 are sensitive) and two cell lines with acquired resistance to temozolomide (A172TR, LN229TR). microRNA-34a reduced proliferation and sensitized to temozolomide (Combination Index< 0.2–0.6) and radiation (dose enhancement factor 1.7–2.2) treatment, regardless of baseline treatment resistance in all studied cell lines. We identified broadly conserved microRNA-34a binding sites in the 3'UTR of multiple mRNAs in the Glioblastoma deregulated networks and genes known to confer therapeutic resistance and validated the direct downregulation of Bcl-2 protein as a major contributor to temozolomide sensitization. Nanocells (400nm diameter), termed EDV, were derived from genetically modified bacteria, provided with a bispecific antibody targeting EGFR and loaded with microRNA-34a. EDVs were injected intravenously while temozolomide was administered by oral gavage in GBM6 orthotopic mouse model. We observed significant increases in miR-34a expression, downregulation of oncogenes and reduction in tumor growth in mice treated with microRNA-34a EDV relative to control EDV(p=0.021). Further, microRNA-34a EDV significantly improved survival and synergized with temozolomide therapy [p<0.001, median survival of control EDV, microRNA-34a EDV, control EDV with temozolomide and microRNA-34a EDV with temozolomide was 44, 48, 86 and 165+ days respectively]. In conclusion, microRNA-34a EDV counteracts therapeutic resistance and intra-tumor heterogeneity.